A CRITICAL REFLECTION ON THE SOUTH AFRICAN LAW OF THE CHILD - RB Bernard; MC Buthelezi (Obiter, 2014)
Children are considered to be vulnerable, and therefore need to be protected against parents, strangers and even themselves. As a consequence, the State’s quest for the protection of children in South Africa is expressed in the implementation of legislation designed to offer greater care and protection. For instance, section 28 of the Constitution of the Republic of South Africa, 1996, offers a wide range of rights which are designed to offer greater protection to children. The rights of children can, in effect, be categorized into two themes. The first relates to the protection of children – as the child is dependent on those around him or her due to a lack of capacity, and is therefore vulnerable. The second theme relates to the autonomy of children. Section 28(2) of the Constitution provides that in any matter concerning a child, the best interests of the child are of paramount importance. However, most South African legislative provisions that deal with minor children seem to miss this principle, and are riddled with inconsistencies. In many statutes, where the principle is recognized, there is either limited appreciation of the significance of the principle and its overall impact on issues concerning children, or there is no coherence with the manner the courts have interpreted and applied the principle. For example, the recent judgment of  the Teddy Bear Clinic case declared sections 15 and 16 of the Criminal Law (Sexual Offences and Related Matters) Amendment Act unconstitutional. The judgment has been heavily criticized by different segments of society for encouraging teens to engage in wanton sexual intercourse, but illustrates some of the flaws in legislation aimed at protecting the welfare of minor children in South Africa. Furthermore, the common law and other legislation such as the Choice on Termination of Pregnancy Act, the Marriage Act, and provisions of the Children’s Act regulating contraceptives and condoms, all contain such inconsistencies. For instance, the common law and section 24 (together with s 26) of the Marriage Act allow a minor from the age of puberty to enter into a valid marriage; section 129 of the Children’s Act requires that a minor aged twelve be assisted by a guardian to undergo a surgical operation; whereassections of the Choice Act do not require parental consent for terminating a minor’s pregnancy. This note reviews the above and other inconsistences currently prevalent in the law of the child in South Africa. A brief overview of the Teddy Bear Clinic case will be considered. Thereafter, it outlines and examines various gender-based contradictions in the law, and examines the possible rationale for justifying the particular legislative measure concerned. The note concludes by proposing possible solutions to the discrepancies that have been identified.